Nanosheet-like particles of polythiophene compound and method for producing same

By forming a superswelling layered phase of a bimolecular film in a solvent and oxidative polymerization, nanosheet-like particles of polythiophene-based compounds were successfully prepared, solving the problem of insufficient film thickness in the prior art, and achieving efficient preparation of nano-scale polythiophene-based compounds.

CN119894959APending Publication Date: 2025-04-25THE JAPAN SCI & TECH AGENCY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202380066248.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-10-14
Filing Date
2023-08-15
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The prior art is difficult to form a polythiophene-based compound thin film of 10 nm or less, and there is a lack of a method for forming nanosheet-like particles of polythiophene-based compound.

Method used

By forming a superswelling layered phase of a bimolecular film in a solvent, a thiophene-based compound is added to the solvent to form a layer of a thiophene-based compound, and the oxidative polymerization is performed using an oxidative polymerization catalyst to form nanosheet-like particles of a polythiophene-based compound.

Benefits of technology

The polythiophene-based compound nanosheet-like particles and dispersion liquid with a thickness of 0.5 nm or more and 10 nm or less are obtained, and the problem of insufficient film thickness is solved, and a dispersion liquid of nanosheet-like particles that are stable in the non-aggregation are provided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005311977320000091
    Figure BDA0005311977320000091
  • Figure BDA0005311977320000141
    Figure BDA0005311977320000141
  • Figure BDA0005311977320000142
    Figure BDA0005311977320000142
Patent Text Reader

Abstract

Provided are nanoflake-like particles of a polythiophene compound having a thickness of 10 nm or less, which cannot be obtained by conventional methods, and a method for producing the nanoflake-like particles. In particular, provided is a dispersion liquid composition containing nanoplatelets of a polythiophene compound, which exist stably without aggregation. This nanosheet-shaped particle of a polythiophene compound has a thickness of 0.5 nm or more and 10 nm or less, and an aspect ratio (maximum width in the particle / thickness) of 100 or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to nano-plate-like particles of polythiophene compounds and a method for producing the same.

[0002] This application claims priority based on Japanese Patent Application No. 2022-165782 filed in Japan on October 14, 2022, the contents of which are incorporated herein. Background Art

[0003] Polythiophene has a polymer structure formed by connecting π conjugated systems, so it has electrical conductivity, excellent processability, and high environmental stability and thermal stability. Therefore, in recent years, polythiophene has attracted attention as a material that can be used for electrical components, such as organic thin film solar cells, organic thin film transistors, photoelectric conversion materials, organic EL materials, diodes, triodes, electro-optical displays, reflective films, nonlinear optical materials, etc.

[0004] As a method for producing polythiophene, various methods have been reported, and a method for producing by polymerizing thiophene using a catalyst for polythiophene polymerization can be generally cited. For example, as a method for producing poly(3,4-ethylenedioxythiophene) (PEDOT) as a derivative of polythiophene, a method can be cited in which an oxidizing agent suitable for oxidative polymerization of pyrrole, such as a trivalent iron salt, an alkali metal persulfate, and ammonium persulfate, is used in an aqueous solution of polystyrene sulfonic acid to obtain 3,4-ethylenedioxythiophene (EDOT) by oxidative polymerization (for example, Patent Document 1). PEDOT is insoluble, so in the above-mentioned production method, it is obtained in a state contained in a dispersion of colloidal particles. In addition, as a method for forming a thin film of PEDOT, a method can be cited in which an EDOT monomer, a trivalent iron salt of p-toluenesulfonic acid as an oxidative polymerization agent, a low-temperature curing adhesive, and a solvent are directly polymerized on a supporting substrate (for example, Patent Document 1). As a film-forming method of a liquid containing an EDOT raw material, a gel film-forming process, a drop coating method, a spin coating method, etc. can be cited. The film thickness of the PEDOT thin film obtained by this film formation method is in the range of several tens of nm to several hundreds of nm to several μm (for example, Non-Patent Document 1 and Patent Document 2).

[0005] On the other hand, various methods have been studied for the production of nano-flaky particles. For example, the following method is disclosed: when a bimolecular membrane forms a super-swollen lamellar phase in a solvent, a sheet-like metal organic structure is formed between two monolayers constituting one bimolecular membrane, thereby producing metal organic structure nano-flaky particles (for example, Patent Document 3). In addition, for example, the following method is disclosed: when a bimolecular membrane forms a super-swollen lamellar phase in a solvent, a precursor (aluminosilicate) of zeolite is formed between two monolayers constituting one bimolecular membrane, thereby producing zeolite nano-flaky particles (for example, Patent Document 4).

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Laid-Open No. 1-313521

[0009] Patent Document 2: Japanese Patent Application Publication No. 2011-181724

[0010] Patent Document 3: International Publication No. 2018 / 016650

[0011] Patent Document 4: International Publication No. 2020 / 250985

[0012] Non-patent literature

[0013] Non-patent document 1: Draft lectures of the 65th Spring Academic Conference of the Society of Applied Physics (2018 Waseda University, Nishi-Waseda Campus), lecture number: 18p-P3-11 Summary of the invention

[0014] Problems to be solved by the invention

[0015] However, the method of forming a thin film by directly polymerizing a liquid containing an EDOT raw material after film formation has problems such as difficulty in forming a thin film of 10 nm or less and the need for expensive equipment.

[0016] Furthermore, Patent Documents 3 and 4 do not disclose a method for forming a layer of a monomer such as EDOT and then polymerizing it to form nanosheet particles of a polymer such as PEDOT. In particular, they do not disclose a method for forming nanosheet particles of a polythiophene-based compound.

[0017] The present invention has been made in view of the above circumstances, and an object thereof is to provide nano-plate-like particles of a polythiophene-based compound and a method for producing the same. Another object is to provide a dispersion liquid containing nano-plate-like particles of a polythiophene-based compound.

[0018] Means for solving problems

[0019] In order to solve the above-mentioned problems, the present invention provides the following means.

[0020] [1] Nanoplate-like particles, characterized in that they are nanoplate-like particles of a polythiophene compound,

[0021] The thickness of the nano-plate-like particles is 0.5 nm or more and 10 nm or less.

[0022] The aspect ratio (maximum width / thickness in the particle) of the nanoplate-like particles is 100 or more.

[0023] [2] The nanosheet particles according to [1], wherein the polythiophene compound is poly(3,4-ethylenedioxythiophene).

[0024] [3] The nano-plate-like particle according to [1] or [2], wherein the thickness of the nano-plate-like particle is 1 nm or more and 5 nm or less.

[0025] The width of the nanoplate-like particles in the plane direction is 200 nm or more and 100 μm or less.

[0026] [4] A method for producing nano-plate-like particles of a polythiophene-based compound, comprising:

[0027] A first step is to form a bimolecular membrane in a solvent, add a thiophene compound to the solvent to form a super-swollen lamellar phase of the bimolecular membrane, and thereby form a layer of the thiophene compound between two monomolecular phases constituting one bimolecular membrane; and

[0028] In the second step, the thiophene compound having formed a layer in the first step is subjected to oxidative polymerization using a polymerization catalyst to form nanosheet particles of a polythiophene compound.

[0029] [5] The nanosheet particles according to [4], wherein in the first step, the super-swollen lamellar phase of the bilayer is formed at a temperature of 20° C. to 40° C.

[0030] [6] The method for producing nanosheet particles of a polythiophene compound according to [4] or [5], wherein the thiophene compound is 3,4-ethylenedioxythiophene,

[0031] The polythiophene compound is poly(3,4-ethylenedioxythiophene).

[0032] [7] The method for producing nanoplate particles of a polythiophene compound according to [4] or [5], wherein the polymerization catalyst is iron (III) chloride.

[0033] [8] The method for producing nano-plate-like particles of a polythiophene-based compound according to [4] or [5], wherein the solvent is a solvent containing only water or a mixed solvent containing a hydrocarbon-based solvent and water,

[0034] The mass ratio of the hydrocarbon solvent to water in the aforementioned solvent is hydrocarbon solvent:water=0:100 to 15:85.

[0035] [9] The method for producing nanoplate particles of a polythiophene compound according to [4] or [5], wherein the solvent is a mixed solvent containing a hydrocarbon solvent and water.

[0036] The mass ratio of the hydrocarbon solvent to water in the aforementioned solvent is hydrocarbon solvent:water=0.01:99.99 to 15:85.

[0037]

[10] The method for producing nanoplate particles of a polythiophene-based compound according to [9], wherein the hydrocarbon solvent is hexane.

[0038]

[11] The method for producing nanosheet particles of a polythiophene-based compound according to any one of [4] and [5], wherein the amphiphilic substance constituting the bimolecular membrane is polyethylene glycol monoalkyl ether.

[0039]

[12] The method for producing nanoplate particles of a polythiophene-based compound according to

[11] , wherein the polyethylene glycol monoalkyl ether is tetraethylene glycol monomethyl ether.

[0040]

[13] The method for producing nanoplate particles of a polythiophene-based compound according to

[11] , wherein the polyethylene glycol monoalkyl ether is tetraethylene glycol monododecyl ether having a number average molecular weight of 362 or less.

[0041]

[14] The method for producing nanoplate particles of a polythiophene-based compound according to [4] or [5], wherein the solvent contains a monohydric alcohol.

[0042]

[15] The method for producing nanoplate particles of a polythiophene-based compound according to

[14] , wherein the monohydric alcohol is at least one selected from the group consisting of 1-propanol, 2-propanol, and 1-butanol.

[0043]

[16] The method for producing nanoplate particles of a polythiophene-based compound according to

[15] , wherein the monohydric alcohol is 1-propanol.

[0044]

[17] The method for producing nanoplate particles of a polythiophene-based compound according to

[15] , wherein the content of the monohydric alcohol in the solvent is 0.1% by mass or more and 10% by mass or less.

[0045]

[18] The method for producing nano-plate-like particles of a polythiophene-based compound according to [4] or [5], wherein the thickness of the nano-plate-like particles is 0.5 nm or more and 10 nm or less.

[0046] The width of the nano-plate-like particles in the plane direction is 200 nm or more and 100 μm or less.

[0047] The aspect ratio (maximum width / thickness in the particle) of the nanoplate-like particles is 100 or more.

[0048]

[19] A dispersion composition comprising the nano-plate-like particles according to [1] or [2].

[0049]

[20] The dispersion composition according to

[19] , further comprising a monohydric alcohol and containing substantially no water.

[0050] Effects of the Invention

[0051] The present invention can provide nano-plate-shaped particles of a polythiophene compound having a thickness of 10 nm or less, which cannot be obtained by conventional methods, and a method for producing the same. In particular, it can provide a dispersion composition containing nano-plate-shaped particles of a polythiophene compound that are stable without aggregation. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] [ Figure 1 ] is the AFM data of the nanosheet particles of the polythiophene compound obtained in Example A-1.

[0053] [ Figure 2 ] is the AFM data of the nanosheet particles of the polythiophene compound obtained in Example A-1.

[0054] [ Figure 3 ] is the FT-IR spectrum of the nanosheet particles of the polythiophene compound obtained in Example A-1.

[0055] [ Figure 4 ] is a TEM image of the nanosheet particles of the polythiophene compound obtained in Example A-1.

[0056] [ Figure 5 ] is a TEM image of the nanosheet particles of the polythiophene compound obtained in Example A-1.

[0057] [ Figure 6 ] is a TEM image of the nanosheet particles of the polythiophene compound obtained in Example A-1.

[0058] [ Figure 7 ] is the DLS data of the nanosheet particles of the polythiophene compound obtained in Example A-1.

[0059] [ Figure 8 ] is the SEM-EDX data of the nano-sheet particles of the polythiophene compound obtained in Example A-1.

[0060] [ Fig. 9 ] is the TG data of the nanosheet particles of the polythiophene compound obtained in Example A-1.

[0061] [ Fig.10 ] is the AFM data of the nanosheet particles of the polythiophene compound obtained in Example D-1.

[0062] [ Fig.11] is the AFM data of the nanosheet particles of the polythiophene compound obtained in Example D-1.

[0063] [ Fig.12 ] is a TEM image of the nanosheet particles of the polythiophene compound obtained in Example D-1.

[0064] [ Fig.13 ] is the DLS data of the nanosheet particles of the polythiophene compound obtained in Example D-1.

[0065] [ Fig.14 ] is a photograph showing the test results of the coating properties of PEDOT nano-plate particles.

[0066] [ Fig.15 ] is a photograph showing the test results of the coating properties of PEDOT bulk particles.

[0067] [ Fig.16 ] is a schematic diagram showing the coating properties of PEDOT nanosheet particles.

[0068] [ Fig.17 ] is a schematic diagram showing the coating properties of PEDOT bulk particles.

[0069] [ Fig.18 ] is a photograph showing the test results for evaluating the effect of manufacturing conditions (pH) on the appearance of PEDOT nano-sheet particles.

[0070] [ Fig.19 ] is a graph showing the test results for evaluating the effect of production conditions (pH) on the yield of PEDOT nanosheet particles.

[0071] [ Fig. 20 ] is a photograph showing the test results for evaluating the effect of production conditions (addition of SDS) on the yield of PEDOT nanosheet particles. DETAILED DESCRIPTION

[0072] Hereinafter, nanoplate particles of polythiophene compounds and a method for producing the same according to an embodiment of the present invention will be described. It should be noted that the present embodiment is specifically described for better understanding of the gist of the invention and does not limit the present invention unless otherwise specified.

[0073] (Nano-sheet particles of polythiophene-based compounds)

[0074] The nano-flaky particles of a polythiophene compound according to one embodiment of the present invention (also referred to as nano-flaky particles of the present embodiment) are nano-flaky particles formed of a polythiophene compound. The thickness of the nano-flaky particles of the present embodiment is 0.5 nm or more and 10 nm or less. The aspect ratio of the nano-flaky particles is 100 or more. Here, the aspect ratio refers to the ratio of the maximum width to the thickness in the particle (maximum width / thickness). The thickness of the nano-flaky particles is preferably 1 nm or more and 5 nm or less. The width of the nano-flaky particles in the plane direction can be 200 nm or more and 100 μm or less.

[0075] It should be noted that the "thiophene compound" herein refers to thiophene or its derivatives (eg, including thiophene which may have a substituent). In addition, the "polythiophene compound" refers to polythiophene or its derivatives (eg, including polymers of the above thiophene compounds).

[0076] The nano-plate-like particles of this embodiment are excellent in uniformity of thickness and aspect ratio, and have high flexibility and high adhesion due to their ultra-thinness.

[0077] The nanosheet particles of this embodiment are not limited to the particles obtained by the "method for producing nanosheet particles of polythiophene-based compounds" described later, but are preferably nanosheet particles having the same size, dispersion characteristics, or conductivity as the particles obtained by the "method for producing nanosheet particles of polythiophene-based compounds" described later, and more preferably nanosheet particles obtained by the "method for producing nanosheet particles of polythiophene-based compounds" described later.

[0078] The nanosheet particles of this embodiment are not limited in their existence form (bulk state), and examples thereof include a state dispersed in a fluid medium, a powder state, a thin film state formed on a supporting substrate, and a state of independent sheets.

[0079] The nano-sheet particles of the present embodiment, for example, when produced by the "method for producing nano-sheet particles of polythiophene-based compounds" described later, may be nano-sheet particles in a monodisperse state before the solution is removed, or may be secondary particles formed by aggregating (e.g., stacking) the nano-sheet particles in a monodisperse state as primary particles. For example, based on the measurement results of TEM and AFM shown in the examples described later, it can be determined that it is a single nano-sheet particle as a primary particle.

[0080] The width of the above-mentioned nano-flaky particles in the plane direction is not particularly limited, and can be more than 200nm and less than 100μm. In addition, for example, in the case of being manufactured by the "method for producing nano-flaky particles of polythiophene-based compounds" described later, the nano-flaky particles in a monodisperse state (for example, particles with a width in the plane direction of more than 200nm and less than 100μm) can be formed into a film on a substrate to form nano-flaky particles. The nano-flaky particles here are sheets with a thickness of more than 0.5nm and less than 10nm (preferably more than 1nm and less than 5nm), and the width in the plane direction can be greater than 100μm. The nano-flaky particles of this embodiment can include such nano-flaky particles.

[0081] [Polythiophene compounds]

[0082] The polythiophene compound of one embodiment of the present invention (also referred to as the polythiophene compound of the present embodiment) refers to a polymer compound having a structure including a polymer of a thiophene compound, and a polymer compound having thiophene as a partial skeleton. The degree of polymerization of the polythiophene compound of the present embodiment can be estimated by assuming that a sheet of nanosheet particles of the present embodiment is composed of one molecule and performing an estimation method. For example, as an example of the polythiophene compound of the present embodiment, it can be a polymer compound having a structure including a polymer of a thiophene compound having more than 150,000 polymers and less than 15 million polymers, and a polymer compound having thiophene as a partial skeleton. The aforementioned thiophene compound is preferably at least one selected from the group consisting of thiophenes and their derivatives. The polythiophene compound of the present embodiment can be at least one polymer selected from the group consisting of the aforementioned thiophenes and their derivatives, and can be at least one selected from the group consisting of polythiophenes and their derivatives.

[0083] As the thiophene compound involved in the present embodiment, thiophene, 3-methylthiophene, 3-ethylthiophene, 3-propylthiophene, 3-butylthiophene, 3-hexylthiophene, 3-heptylthiophene, 3-octylthiophene, 3-nonylthiophene, 3-decylthiophene, 3-methoxythiophene, 3-ethoxythiophene, 3-butoxythiophene, 3-methyl-4-methoxythiophene, 3,4-ethylenedioxythiophene, benzothiophene, benzodithiophene, etc. can be mentioned. Among them, 3,4-ethylenedioxythiophene (EDOT) is preferred from the aspects of moderate polymerization rate and excellent heat resistance of the polymer.

[0084] As the polythiophene and its derivatives involved in the present embodiment, homopolymers are preferred. Homopolymers refer to polymers formed by bonding only a plurality of groups selected from the group consisting of thiophene diyl and thiophene diyl with a substituent. As the thiophene diyl, thiophene-2,5-diyl is preferred, and as the thiophene diyl with a substituent, 3,4-ethylenedioxythiophene-2,5-diyl and alkylthiophene-2,5-diyl are preferred. Specific examples of polythiophene and its derivatives as homopolymers include poly (3,4-ethylenedioxythiophene) (PEDOT), poly (3-hexylthiophene-2,5-diyl) (P3HT), poly (3-octylthiophene-2,5-diyl), poly (3-dodecylthiophene-2,5-diyl), and poly (3-octadecylthiophene-2,5-diyl). Among polythiophene homopolymers and derivatives thereof, polythiophene homopolymers composed of thiophenediyl groups substituted with 3,4-ethylenedioxy groups or alkyl groups having 6 to 30 carbon atoms are preferred, and poly(3,4-ethylenedioxythiophene) (PEDOT) represented by the following formula (A) is more preferred.

[0085] [Chemical formula 1]

[0086]

[0087] (Method for producing nanosheet particles of polythiophene-based compounds)

[0088] A method for producing nano-sheet particles of a polythiophene compound according to one embodiment of the present invention (also referred to as the present embodiment) comprises: a first step of forming a layer of a thiophene compound, which is a monomer of the polythiophene compound; and a second step of producing nano-sheet particles of the polythiophene compound by oxidatively polymerizing the thiophene compound from the layer of the thiophene compound.

[0089] Here, the "polythiophene compound" and "thiophene compound" are the same as the "polythiophene compound" and "thiophene compound" described in the above section (Nanoplate-like particles of polythiophene compound), and their preferred examples are also the same.

[0090] <First step>

[0091] In the first step, a layer of a thiophene compound which is a monomer of a polythiophene compound is formed by utilizing a super-swollen lamellar phase.

[0092] A bimolecular membrane is formed in a solvent, and a thiophene compound is added to the solvent to form a super-swollen lamellar phase of the bimolecular membrane. As a result, a layer of the thiophene compound is formed between two monomolecular phases constituting one bimolecular membrane. That is, by forming a super-swollen lamellar phase of the bimolecular membrane, the thiophene compound can be enclosed between two monomolecular phases constituting one bimolecular membrane. Thus, a layer of the thiophene compound is formed between two monomolecular phases constituting one bimolecular membrane.

[0093] In the layer of thiophene-based compounds formed between the two monomolecular phases, for example, monomer molecules of thiophene-based compounds contained in the layer of thiophene-based compounds exist in a super-swollen lamellar phase in a substantially non-aggregated state. The molecules of the thiophene-based compounds can be arranged in a thin two-dimensional plane space formed between the two monomolecular phases. The molecules of the thiophene-based compounds in the thin two-dimensional plane space can have a certain orientation or a random orientation. In addition, a layer of thiophene-based compounds formed between a pair of the two monomolecular phases can also be arranged in the thickness direction of the layer with a layer of thiophene-based compounds formed in the same manner to form a stacked structure.

[0094] It should be noted that the layer of the thiophene compound formed between the two monomolecular phases in this way provides the following effects to the "polythiophene compound" (i.e., the nano-sheet particles of the present embodiment) obtained after the subsequent polymerization: high orientation is given in the arrangement state of the polythiophene compound, and the insulating effect caused by the presence of the space between molecules is suppressed (i.e., high conductivity is exhibited). As a result, the "polythiophene compound" (i.e., the nano-sheet particles of the present embodiment) obtained after the polymerization can be provided with excellent uniformity of thickness and aspect ratio, as well as high flexibility and high adhesion due to its thinness.

[0095] In addition, a layer of thiophene compounds (monomer layer) formed between two monomolecular phases forms a "polythiophene compound" (i.e., the nanosheet particles of the present embodiment) through a subsequent polymerization reaction. Since the space for the polymerization reaction is limited, it is predicted that it will grow in the planar direction. In addition, if the physical properties of the polythiophene compound are taken into consideration, a nanosheet particle can be formed from one polymer. In addition, a nanosheet particle can also be formed by stacking several polymers. With respect to the state and configuration of the polymer of the polythiophene compound in the nanosheet particles, in the case where the nanosheet particles of the present embodiment contain polythiophene compounds and are the above-mentioned nanosheet particles, the state and configuration of the polymer in the nanosheet particles are not limited.

[0096] In this embodiment, a super swollen lamellar phase is first formed, and then the thiophene compound is added. As a method for forming a super swollen lamellar phase, a bimolecular membrane is formed in a solvent, and an amphiphilic substance is added to the solvent to form a super swollen lamellar phase of the bimolecular membrane.

[0097] The hyper-swollen lamellar phase refers to a specific lamellar phase that swells in a solvent. More specifically, it refers to a phase in which a plurality of bimolecular membranes constituting the lamellar phase are stacked in a lamellar state with a solvent layer sandwiched between them.

[0098] The phase constituting the super-swollen lamellar phase may be observed to be colored by Bragg reflection in the visible light region. The super-swollen lamellar phase may be a hyper-swollen lyotropic lamellar phase.

[0099] In the super swollen lamellar phase, the mass ratio of the solvent in the whole is not particularly limited as long as the purpose of the present invention is met, and is usually 90% by mass or more, preferably 95% by mass or more, more preferably 98% by mass or more, and further preferably 99% by mass or more. The upper limit is not particularly limited as long as it is a range in which a super swollen lamellar phase can be formed between the solute and the solvent, and the limiting concentration at which a super swollen lamellar phase can be formed between the solute and the solvent used is the theoretical upper limit. The aforementioned "whole" refers to the total of all substances mixed, including the solute and the solvent. In the super swollen lamellar phase, the upper limit of the mass ratio of the solvent in the whole can be, for example, 99% by mass.

[0100] In the super-swollen lamellar phase, the distance between adjacent bimolecular membranes (also referred to as "interlayer distance" in this specification) is not particularly limited and can be appropriately set according to the materials used and the target application. It is usually between 50 nm and 1000 nm (including the values ​​at both ends, the same below). In the case of thinning the target nano-flaky particles, the thinner the interlayer distance, the more preferred, for example, preferably less than 500 nm. The interlayer distance between bimolecular membranes refers to the distance from the end of a part of a bimolecular membrane that has an affinity for the solvent to the end of another bimolecular membrane adjacent to the aforementioned bimolecular membrane that has an affinity for the solvent. In addition, the aforementioned interlayer distance may depend on the content of the molecules (amphiphilic molecules) that constitute the bimolecular membrane.

[0101] The thickness of the bimolecular film itself is not particularly limited, but is usually 1 nm to 20 nm, preferably 1 nm to 10 nm, more preferably 1 nm to 5 nm.

[0102] Even in a solution of a nonionic amphiphilic substance, the super-swollen lamellar phase can be stably maintained by the undulation of each layer or Helfrich interaction.

[0103] By enclosing the thiophene compound in the bimolecular membrane of the super-swollen lamellar phase, a layer of the thiophene compound can be produced. In particular, an arranged layer of the thiophene compound can be produced.

[0104] After the super-swollen lamellar phase is formed, the thiophene compound is added to the solvent to form a layer of the thiophene compound between the two monomolecular layers constituting one bimolecular membrane.

[0105] In the method for forming a layer of a thiophene compound, a layer of a thiophene compound is formed between hydrophobic parts of two monolayers constituting one bimolecular membrane by orienting the hydrophilic part toward the solvent side. By changing the combination of the mixed solvent and the amphiphilic molecule, the hydrophobic part and the hydrophilic part of the bimolecular membrane are configured as described above. In this embodiment, since the layer of the thiophene compound is formed between the parts that are non-affinity with the solvent, the layer of the thiophene compound can be produced not only in the hydrophobic reaction area but also in the hydrophilic reaction area depending on the type of the solvent.

[0106] <Solvent>

[0107] The solvent in the present embodiment of the method for producing the thiophene compound layer may be a solvent containing only water, but preferably contains an organic solvent as a solvent other than water. The organic solvent may be a hydrocarbon solvent.

[0108] Examples of hydrocarbon solvents include aliphatic hydrocarbon solvents such as cyclohexane, methylcyclohexane, n-pentane, n-hexane, n-heptane, n-octane, n-nonane, n-decane, n-dodecane, and bicyclohexane; and aromatic hydrocarbon solvents such as toluene, xylene, mesitylene, ethylbenzene, n-hexylbenzene, and cyclohexylbenzene. In addition, the aforementioned solvent may be a hydrocarbon solvent alone or a solvent composed of a hydrocarbon solvent and other organic solvents.

[0109] Examples of the aforementioned other organic solvents include ketone solvents such as acetone, acetylacetone, methyl ethyl ketone, cyclohexanone, and acetophenone; alcohol solvents such as methanol, ethanol, n-propanol, isopropanol, cyclohexanol, ethylene glycol, diethylene glycol, propylene glycol, and glycerol; chlorine solvents such as 1,2-dichloroethane, 1,1,2-trichloroethane, chlorobenzene, and o-dichlorobenzene; ether solvents such as tetrahydrofuran, dioxane, anisole, and 4-methylanisole; and the like.

[0110] When a hydrocarbon solvent and another organic solvent are used as the solvent, the mass ratio of the two is preferably hydrocarbon solvent:other organic solvent=80:20 to 99.99:0.01, more preferably 85:15 to 99.9:0.1.

[0111] In addition, as the solvent in the present embodiment of the method for manufacturing the layer of the aforementioned thiophene compound, for example, when the aforementioned solvent is a solvent containing only water or a mixed solvent containing the aforementioned organic solvent and water, the mass ratio of the two is preferably organic solvent: water = 0: 100 to 15: 85, and more preferably 0: 100 to 10: 90. In addition, when the aforementioned solvent is a mixed solvent containing the aforementioned organic solvent and water, the mass ratio of the two is preferably organic solvent: water = 0.01: 99.99 to 15: 85, and more preferably 0.1: 99.9 to 10: 90. In addition, in these preferred embodiments, as a solvent, an acidic aqueous solution such as hydrochloric acid, nitric acid, sulfuric acid, etc.; an alkaline aqueous solution such as an aqueous sodium hydroxide solution can be used instead of water or in addition to water, depending on the type of reaction when synthesizing the target nano-sheet particles.

[0112] In this embodiment, the organic solvent is preferably a hydrocarbon solvent. The solvent is preferably a mixture of water and a hydrocarbon solvent, more preferably a mixture of water and hexane. The mass ratio of the two is preferably hexane: water = 0.01:99.99 to 15:85, more preferably 0.1:99.9 to 10:90.

[0113] <Amphiphilic Substances>

[0114] In the present embodiment, as the amphiphilic substance, for example, a nonionic amphiphilic substance can be mentioned.

[0115] The amount of the amphiphilic substance added may be 1 to 50 parts by mass, 1 to 10 parts by mass, or 1 to 5 parts by mass relative to 100 parts by mass of the solution (when the surfactant aid is included, the total amount including the surfactant aid).

[0116] "Nonionic amphiphilic substances"

[0117] Examples of the nonionic amphiphilic substance according to the present embodiment include ester-type surfactants, ether-type surfactants, ester ether-type surfactants, alkanolamide-type surfactants, alkyl glycosides, and higher alcohols. Commercially available nonionic amphiphilic substances can be used.

[0118] Examples of the ester-type surfactant include sucrose fatty acid esters such as sucrose laurate, sucrose oleate, and sucrose monopalmitate; sorbitan fatty acid esters such as sorbitan caprylate, sorbitan caprylate diester, sorbitan caproate monoester, sorbitan caproate diester, sorbitan caprate monoester, sorbitan caprate diester, sorbitan laurate monoester, sorbitan laurate diester, sorbitan myristic acid monoester, and sorbitan myristic acid diester; monoglycerol fatty acid esters such as caprylic acid glyceryl, capric acid glyceryl, lauric acid glyceryl, myristic acid glyceryl, and di(lauric acid / myristic acid) glyceryl; monostearic acid diglyceryl, monooleic acid diglyceryl, dioleic acid diglyceryl, monoisostearic acid diglyceryl, monostearic acid tetraglyceryl, tristearic acid tetraglyceryl, pentastearic acid tetraglyceryl, pentaoleic acid tetraglyceryl, monolauric acid diglyceryl Hexaglyceryl monoglyceride, monomyristic acid hexaglyceride, monostearic acid hexaglyceride, monooleic acid hexaglyceride, tristearic acid hexaglyceride, pentastearic acid hexaglyceride, pentastearic acid hexaglyceride, polyricinoleic acid hexaglyceride, monolauric acid decaglyceride, monomyristic acid decaglyceride, monostearic acid decaglyceride, monooleic acid decaglyceride, monolinoleic acid decaglyceride, monoisostearic acid decaglyceride, distearic acid decaglyceride, dioleic acid decaglyceride, diisostearic acid decaglyceride, tristearic acid decaglyceride, trioleic acid decaglyceride, triisostearic acid decaglyceride, pentastearic acid decaglyceride, pentaoleic acid decaglyceride, pentaisostearic acid decaglyceride, heptastearic acid decaglyceride, heptaoleic acid decaglyceride, heptaisostearic acid decaglyceride, decaglyceride decaglyceride, decaglyceride decaglyceride decaglyceride, decaglyceride decaglyceride decaglyceride, decaglyceride decaglyceride decaglyceride, decaglyceride decaglyceride decaglyceride, decaglyceride decaglyceride decaglyceride, decaglyceride decaglyceride decaglyceride, etc.

[0119] Examples of the ether-type surfactant include polyethylene glycol monoalkyl ether (C n E m ) polyethylene glycol monoalkyl ether; polyoxyethylene alkylphenyl ethers such as poly(oxyethylene) octylphenyl ether represented by the following formula (2) and poly(oxyethylene) nonylphenyl ether represented by the following formula (3); and the like.

[0120] [Chemical formula 2]

[0121]

[0122] (In the formula, n represents the number of carbon atoms of the alkyl group of the hydrophobic part, and m represents the number of ethylene oxides of the hydrophilic part. n can be 3 to 40, 5 to 20, or 20 to 14. m can be 1 to 10, 2 to 8, or 3 to 6)

[0123] [Chemical formula 3]

[0124]

[0125] (The number of moles of ethylene oxide added, p, may be 3 to 40, or 5 to 20)

[0126] [Chemical formula 4]

[0127]

[0128] (The number of added moles of ethylene oxide, q, may be 3 to 40, or 5 to 20).

[0129] Examples of the ester-ether type surfactants include polyoxyethylene fatty acid esters such as polyethylene glycol monostearate, polyethylene glycol monooleate, and polyethylene glycol dioleate; polyoxyethylene hexitol fatty acid esters; polyoxyethylene sorbitan fatty acid esters (the sorbitan fatty acid ester portion is the same as the above-mentioned ester-type surfactants), sorbitan fatty acid ester polyethylene glycol (the sorbitan fatty acid ester portion is the same as the above-mentioned ester-type surfactants), and the like.

[0130] Examples of the alkanolamide surfactant include lauric acid monoethanolamide, lauric acid monoisopropanolamide, lauric acid diethanolamide, oleic acid diethanolamide, stearic acid diethanolamide, and fatty acid alkanolamides of cocamide DEA.

[0131] Examples of the alkyl glycoside include n-octyl-β-D-glucoside, n-octyl-β-D-maltoside, n-decyl-β-D-glucoside (decyl glucoside), n-decyl-β-D-maltoside, n-undecyl-β-D-glucoside, n-dodecyl-β-D-glucoside (lauryl glucoside), n-tridecyl-β-D-glucoside, n-octadecyl-β-D-glucoside, n-heptyl-β-D-thioglucoside, n-octyl-β-D-thioglucoside, and n-nonyl-β-D-thiomaltoside.

[0132] Examples of the higher alcohol include higher alcohols having 12 to 18 carbon atoms, such as cetyl alcohol, stearyl alcohol, lauryl alcohol, and oleyl alcohol.

[0133] In a preferred embodiment, the nonionic amphiphilic substance may be a polyethylene glycol monoalkyl ether (C n E m )constitute.

[0134] [Chemical formula 5]

[0135]

[0136] (wherein n and m have the same meanings as above)

[0137] Examples of the polyethylene glycol monoalkyl ether include tetraethylene glycol monomethyl ether and tetraethylene glycol monododecyl ether.

[0138] In a certain embodiment, in the above formula (1), 2 < n / m < 6, 2.2 < n / m < 5, or 2.4 ≤ n / m ≤ 4 is possible. The lower limit value of n / m is not particularly limited and can be 2, 2.2, or 2.4. The upper limit value of n / m is not particularly limited and can be 6, 5, 4, or 3. The nonionic amphiphilic substance involved in this embodiment is preferably tetraethylene glycol monododecyl ether (C12E4). As tetraethylene glycol monododecyl ether (C12E4), for example, polyethylene glycol dodecyl ether (Brij (registered trademark) L4 manufactured by Sigma-Aldrich Co., Ltd.) used in the following examples can be cited.

[0139] [Surfactant adjuvant]

[0140] In addition, in this embodiment, in order to stabilize the amphiphilic substance, the solvent may contain a surfactant adjuvant. As the surfactant adjuvant, monohydric alcohols, glycol-based polyhydric alcohols and their derivatives, etc. can be cited. In this embodiment, the solvent particularly preferably contains a monohydric alcohol.

[0141] As the monohydric alcohol, for example, ethanol, n-propanol, isopropanol, n-butanol, sec-butanol, isobutanol, tert-butanol, 1-pentanol, 2-pentanol, 3-pentanol, 2-methyl-1-butanol, isopentanol, tert-pentanol, 3-methyl-2-butanol, neopentanol, 1-hexanol, 1-heptanol, 1-octanol, 1-nonanol, 1-decanol, 2-methyl-1-pentanol, 4-methyl-2-pentanol, 2-ethyl-1-butanol, 2-heptanol, 3-heptanol, 2-octanol, 2-ethyl-1-hexanol, 3,5,5-trimethyl-1-hexanol and other monohydric alcohols having 1 to 10 carbon atoms; cholesterol, cholesteryl oleyl succinate, cholestanol, cholesterol esters having a saturated or unsaturated straight-chain or branched hydrocarbon group with 12 to 36 carbon atoms (preferably 14 to 28 carbon atoms), cholesterol derivatives such as dehydrocholesterol, etc.

[0142] As the glycol-based polyhydric alcohol or its derivative, for example, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, propylene glycol-1-methyl ether, ethylene glycol diethyl ether, ethylene glycol dimethyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monobutyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, triethylene glycol dimethyl ether and other glycol ethers; glycol ether acetates such as ethylene glycol methyl ether acetate, diethylene glycol ethyl ether acetate; diols such as ethylene glycol, propylene glycol, 1,3-butanediol, diethylene glycol, dipropylene glycol, hexanediol; polyhydric alcohols such as glycerol, pentaerythritol, sorbitol, etc.

[0143] In this embodiment, the solvent is a mixed solvent of a hydrocarbon solvent such as hexane and water, and the amphiphilic substance is a nonionic amphiphilic substance such as polyethylene glycol monoalkyl ether (CnEm). In addition, the solvent may contain a surfactant auxiliary such as a monohydric alcohol.

[0144] The layer of the thiophene-based compound according to this embodiment may contain other compounds.

[0145] The formation temperature of the super swollen lamellar phase in the present embodiment is preferably 15°C to 60°C, more preferably 20°C to 40°C, further preferably 25°C to 35°C, and further preferably 28°C to 32°C.

[0146] In the first step involved in the present embodiment, the pH in the system for forming the super-swollen lamellar phase of the bimolecular membrane can be controlled in advance. For example, a buffer solution pre-adjusted to a desired pH can be used instead of water used as a solvent. As the pH of the mixed solution in the aforementioned system, for example, a value in the range of 2 to 7 can be cited. Preferably, a value in the range of 2 to 4 can be cited.

[0147] In the first step involved in the present embodiment, sodium dodecyl sulfate (hereinafter referred to as SDS) may be added to the system of the super-swollen lamellar phase for forming the bimolecular membrane. For example, the concentration of SDS in the mixed solution in the aforementioned system may preferably be a value of 0.15% by mass or less.

[0148] [Specific example of the first step]

[0149] A preferred example of the first step of the production method according to the present embodiment will be described.

[0150] The reagents and conditions used were as follows.

[0151] Thiophene compounds: for example, 3,4-ethylenedioxythiophene (EDOT)

[0152] Solvent: For example, water or a mixture of hexane and water

[0153] Surfactant: 1-propanol

[0154] Amphiphilic substances: for example, tetraethylene glycol monododecyl ether (C12E4)

[0155] Formation temperature: For example, 25℃~35℃

[0156] Stirring time: e.g. 15 to 30 hours

[0157] Stirring speed: For example, 100-500 rpm

[0158] First, a thiophene compound, an amphiphilic substance, a surfactant, and a solvent are mixed. The mixing order of the reagents is not particularly limited. For example, the thiophene compound, the amphiphilic substance, the surfactant, and the solvent can be mixed in this order. The obtained mixed solution is stirred at a prescribed stirring temperature. Depending on the stirring device, the stirring speed can be different. For example, when a heating stirrer is used, it can be 100 to 500 rpm, or 200 to 400 rpm.

[0159] In the mixed solution, the amounts of each reagent and the like added may be, for example, as follows.

[0160] The aforementioned thiophene compound may be 0.05 to 0.5% by mass, or 0.10 to 0.2% by mass;

[0161] The aforementioned amphiphilic substance: can be 2.5 to 7.5% by mass, can be 4.0 to 5.0% by mass;

[0162] The aforementioned solvent: can be 5.0 to 8.0% by mass, can be 6.0 to 7.0% by mass;

[0163] Water: 70.0 to 95.0% by mass, or 86.0 to 90.0% by mass.

[0164] In adjusting the thickness of the layer of the thiophene compound, the thickness of the bilayer, the raw material composition ratio, the reaction temperature, the reaction time and other conditions can be appropriately combined to adjust. In addition, for example, the formation of the super-swollen lamellar phase can be confirmed by confirming the texture derived from the super-swollen lamellar phase using a polarizing plate.

[0165] <Second step>

[0166] In the second step according to the present embodiment, an oxidative polymerization catalyst is added to the solution as a polymerization catalyst to cause oxidative polymerization of the thiophene compound to produce nanosheet particles of the polythiophene compound.

[0167] 〔Polymerization catalyst〕

[0168] The polymerization catalyst involved in this embodiment is not particularly limited as long as it can polymerize the aforementioned thiophene compound in the layer of the aforementioned thiophene compound obtained in the first step to synthesize a polythiophene compound. As the polymerization catalyst involved in this embodiment, for example, an oxidative polymerization catalyst is preferred. As the oxidative polymerization catalyst, for example, known oxidants such as iron (III) chloride, iron p-toluenesulfonate, copper perchlorate, palladium acetate, and copper acetate can be cited.

[0169] In the second step according to the present embodiment, the reaction conditions for synthesizing the polythiophene-based compound using the polymerization catalyst are not particularly limited, but are preferably within the following ranges.

[0170] Reaction temperature: can be 25-40°C, can be 30-35°C.

[0171] The amount of the polymerization catalyst added may be, for example, 0.05 to 0.2 parts by mass, or 0.075 to 0.12 parts by mass, relative to 100 parts by mass of the mixed solution obtained in the first step.

[0172] In the second step according to the present embodiment, the polymerization reaction time may be 8 to 48 hours, or 12 to 24 hours. The completion of the polymerization reaction may be confirmed by infrared spectroscopy.

[0173] In the second step of the present embodiment, the pH of the reaction region for oxidative polymerization of the thiophene compound forming the layer using a polymerization catalyst can be controlled in advance. For example, a buffer solution pre-adjusted to a desired pH can be used instead of water used as a solvent. Regarding the pH of the mixed solution as the above-mentioned reaction region, for example, a value in the range of 2 to 7 can be cited. Preferably, a value in the range of 2 to 4 can be cited.

[0174] When the pH of the reaction zone is lowered, the oxidizing agent (e.g., Fe 3+ ) becomes higher, the oxidizing ability of the oxidant can be expected to be improved, and as a result, the above-mentioned oxidative polymerization can be promoted.

[0175] In the second step of the present embodiment, SDS may be added to the reaction region for oxidative polymerization of the layered thiophene compound using a polymerization catalyst. For example, the concentration of SDS in the mixed solution in the reaction region is preferably 0.15% by mass or less.

[0176] If a small amount of SDS is present in the reaction zone, it is expected that it will act as an oxidizing agent (e.g., Fe 3+ ) is attracted by the electrostatic attraction of the SDS, and as a result, the aforementioned oxidative polymerization can be promoted.

[0177] <Third step>

[0178] The method for producing nano-flake particles according to the present embodiment preferably further includes a third step.

[0179] In the third step, the solution containing the nano-flaky particles obtained in the aforementioned second step is solvent-removed and dried. The obtained dry solid can be a powdery, granular or other shaped molded body, or can be a form supported on a substrate. In order to make the dry solid granular, known granulation methods such as extrusion, spray drying, stirring granulation, and tumbling granulation can be used.

[0180] For example, the aforementioned solvent, the aforementioned surfactant, the aforementioned amphiphilic substance, or the aforementioned polymerization catalyst added in the first step can be removed by centrifugation. Ethanol and water are used as solvents for washing. The added solvent, water, surfactant, and amphiphilic substance are removed by ethanol, and the polymerization catalyst is removed by water. A dispersion of ethanol or the like of the nano-sheet particles of this embodiment can be prepared without drying after washing. In addition, drying can also be performed. In this case, for example, it can be left to stand in an oven set to a certain drying temperature to volatilize the solvent. The drying temperature can be appropriately adjusted in relation to the drying time, and if drying is performed, it is not particularly limited. For example, it can be 50 to 95°C, or 80 to 95°C.

[0181] It should be noted that, in the nano-sheet particles of the present embodiment obtained in this manner, the polythiophene compound is preferably arranged in a regular arrangement so as to have high orientation and suppress the insulating effect caused by the space between molecules (i.e., exhibit high conductivity). In addition, such nano-sheet particles have excellent uniformity of thickness and aspect ratio, and have high flexibility and high adhesion due to their thinness.

[0182] By the way, when using previous film-forming methods such as drop coating and spin coating, when the surface fine structure of the nanosheet particles of thiophene compounds after film formation is observed in the form of STM images, the layer of thiophene compounds presents an irregular granular structure and has weak orientation, and differences caused by different positions are often observed.

[0183] (Dispersion composition containing nano-plate-like particles of a polythiophene-based compound)

[0184] A dispersion composition containing nano-flaky particles of a polythiophene compound according to one embodiment of the present invention (the dispersion composition of the present embodiment) is a dispersion composition containing the aforementioned nano-flaky particles of a polythiophene compound. Alternatively, the dispersion composition of the present embodiment is a dispersion composition containing nano-flaky particles of a polythiophene compound obtained by the aforementioned method for producing nano-flaky particles of a polythiophene compound.

[0185] The dispersion composition of the present embodiment preferably also contains a monohydric alcohol, and is substantially free of water. Here, "substantially free of water" means that the aforementioned dispersion composition contains less than 10% by mass, preferably less than 5% by mass, and more preferably less than 2% by mass of water. In addition, it may contain more than 0.0001% by mass (1ppm) of water. The aforementioned monohydric alcohol can be given by a specific example of the same monohydric alcohol as described in the aforementioned method for producing nano-flaky particles of the present embodiment. The monohydric alcohol contained in the dispersion composition of the present embodiment may be the same as the monohydric alcohol used as a surfactant in the method for producing nano-flaky particles of the present embodiment, or it may be different.

[0186] In the dispersion composition of the present embodiment, the content of the nano-flaky particles of the present embodiment may be 0 to 100% by mass, or 0 to 1% by mass.

[0187] Examples of a method for producing the dispersion composition of the present embodiment include a method of adding a monohydric alcohol to a solution containing nanoflake particles obtained after the second step of the method for producing nanoflake particles of the present embodiment, and then removing water from the solution.

[0188] [Applications of Nano-Flake Particles]

[0189] Examples of uses of the nanosheet particles of the present embodiment include use as conductive polymer nanosheet materials, thermoelectric conversion thin film materials, organic strain sensors, and biological information monitors.

[0190] <Conductive polymer nanosheet materials>

[0191] Regarding the use as a conductive polymer nanosheet material, specifically, for example, antistatic films, solid electrolytic capacitors, organic electroluminescent products, organic solar cells, organic transistors, transparent electrodes, etc. can be cited. Incidentally, as an example, the conductivity can be 0.1 S / cm to 10000 S / cm, preferably 1 S / cm to 1000 S / cm.

[0192] <Thermoelectric Conversion Thin Film Materials>

[0193] Regarding the use of thermoelectric conversion film materials, specifically, for example, from daily products such as automobiles and home appliances to large-scale facilities such as power plants and factories, among the thermoelectric conversion materials that recover a portion of the waste heat emitted to the atmosphere and reuse it as electrical energy, there are sheets or fibers that take advantage of their flexible properties, namely, adhesive-type thermoelectric power generation sheets (for example, utilizing exhaust heat from factory pipes), independent power supplies for IoT sensors (for example, utilizing exhaust heat from home appliances), etc.

[0194] <Organic strain sensor>

[0195] Regarding the use of organic strain sensors, specifically, for example, in order to produce artificial organs that can reproduce activities similar to those of biological organs, it is necessary to accurately measure the deformation of soft biological tissues. Examples include products such as sensors for measuring strain data generated on the surface of the biological tissues, and the field of hybrid artificial organs that combine the sensors with cells and tissues.

[0196] <Biological Information Monitor>

[0197] Regarding the use as a biological information monitor, specifically, for example, there are ultra-thin electrodes (i.e., electronic nano-bandages) that can be attached to the skin to measure biological electrical signals (e.g., body temperature, pH, heart rate, myoelectric potential), independent power supplies (e.g., using body temperature) for wearable sensor devices not only for daily life but also for health care, medical care, and sports, and the next generation of wearable devices.

[0198] As mentioned above, although the preferred embodiment of the present invention has been described in detail, the present invention is not limited to the specific embodiment, and various modifications and changes can be made within the scope of the gist of the present invention described in the claims.

[0199] Example

[0200] Hereinafter, the present invention will be described in more detail with reference to Examples and Comparative Examples, but the present invention is not limited to the following Examples.

[0201] (Evaluation method)

[0202] [AFM (Atomic Force Microscopy)]

[0203] Device: Veeco Instruments, Inc. Trade name: MMAFM-2

[0204] Measurement conditions: room temperature, atmospheric atmosphere

[0205] Preparation of samples for evaluation: Add several mg of sample to ethanol and irradiate with ultrasonic waves to prepare ethanol dispersion. Drop the prepared dispersion onto a mica substrate. Absorb the excess dispersion and dry it.

[0206] [FT-IR (Fourier Transform Infrared Spectroscopy)]

[0207] Measurement conditions: room temperature, atmospheric atmosphere

[0208] Apparatus: Made by JASCO Co., Ltd. Trade name: FT / IR-4600

[0209] Preparation of evaluation samples: Sample powder was fixed on a metallic disk.

[0210] [TEM (Transmission Electron Microscopy)]

[0211] Measurement conditions: 1×10 -6 Pa

[0212] Device: Made by Hitachi Co., Ltd. Product name: H-800

[0213] Preparation of evaluation samples: Several mg of a sample was added to ethanol and ultrasonic waves were irradiated to prepare an ethanol dispersion, which was then dropped onto a microgrid for TEM and dried.

[0214] [DLS (Dynamic Light Scattering)]

[0215] Device: Otsuka Electronics Co., Ltd. Product name: ELSZ-2000

[0216] Measurement conditions: room temperature, atmospheric atmosphere

[0217] Preparation of evaluation samples: Several mg of a sample was added to ethanol and ultrasonic waves were irradiated to prepare an ethanol dispersion. The prepared dispersion (about 1.5 ml) was placed in a plastic cuvette for DLS and measured.

[0218] [Electrical Conductivity]

[0219] Device: Made by ATTO Co., Ltd. Product name: CROSSPOWER500

[0220] Measurement conditions: room temperature, atmospheric atmosphere

[0221] Preparation of samples for evaluation: Several mg of a sample was added to ethanol and ultrasonic waves were irradiated to prepare an ethanol dispersion, which was then dropped onto a slide glass and dried.

[0222] (Recorded example) 0.0050 g of PEDOT nano-sheet particles are dispersed in 2 g of 0.1 M HCL solution. The obtained mixture is stirred with ultrasound to prepare a dispersion. The dispersion is applied to a glass substrate by a drop coating method and dried to obtain a polythiophene film. The conductivity of the 1 μm thick film obtained in this way is evaluated using a small digital tester. The measurement result is 1 S / cm. Compared with the commercially available PEDOT:PSS measured by the same method, the conductivity is calculated to be about 1 S / cm. The calculation method is to regard the coated part as a rectangular parallelepiped with a height of 1 μm and a width of 1 cm, and measure the resistance at intervals of 1 cm.

[0223] [SEM-EDX (Energy Dispersive X-ray Spectroscopy)]

[0224] Device: Made by JEOL Co., Ltd. Product name: JCM-7000

[0225] Measurement conditions: High vacuum

[0226] Preparation of evaluation samples: Powder samples were attached to carbon tape to prepare the samples.

[0227] [TG (Thermogravimetric Analysis: Thermogravimetric Analysis)]

[0228] Device: Made by Shimadzu Corporation Trade name: DTG-60

[0229] Measurement conditions: Nitrogen atmosphere

[0230] Preparation of evaluation samples: A powder sample (20 mg) was placed in an aluminum cell.

[0231] [Conductivity measurement]

[0232] "Assay Sample Preparation"

[0233] PEDOT bulk particles and PEDOT nanosheet particles were dispersed in water to prepare respective aqueous dispersions (concentration: 3.4×10 -4 g / ml).

[0234] "Measurement method"

[0235] The obtained aqueous dispersion was dripped onto a comb-shaped electrode (Pt, comb teeth pitch 2 μm, manufactured by PSS), and then the electrode was dried. After drying, the conductivity of the electrode was measured using an impedance analyzer (SI1260 model, manufactured by TOYO).

[0236] [Applicability Evaluation]

[0237] "Assay Sample Preparation"

[0238] PEDOT bulk particles and PEDOT nanosheet particles were dispersed in water to prepare respective aqueous dispersions (concentration: 3.4×10 -4 g / ml).

[0239] "Evaluation Method"

[0240] The obtained aqueous dispersion was dripped onto a comb-shaped electrode (made of Pt, with a comb tooth pitch of 2 μm), and then the electrode was dried. After drying, the electrode was visually observed using a research system microscope BX-51 (manufactured by Olympus Corporation).

[0241] Judgment Criteria: The coating properties were evaluated to be excellent if the particles were uniformly dispersed without generating gaps between the particles, the thickness of the particles was substantially uniform, and the particles were closely attached to each other.

[0242] (Example A-1)

[0243] (Production of PEDOT Nanoplate Particles)

[0244] <First step>

[0245] (That is, a first step of forming a bimolecular membrane composed of tetraethylene glycol monododecyl ether having a number average molecular weight of 362 or less in water containing 1-propanol and wherein the content of the 1-propanol is 0.1 mass % or more and 10 mass % or less, adding 3,4-ethylenedioxythiophene to the solvent, forming a super-swollen lamellar phase of the bimolecular membrane under a temperature condition of 20° C. or more and 40° C. or less, and forming a layer of the 3,4-ethylenedioxythiophene between two monomolecular phases constituting one bimolecular membrane)

[0246] <Reagents used and reaction conditions>

[0247] EDOT (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., 0.13 mass%) 0.04 g

[0248] Deionized water (88.6 mass%) 27 g

[0249] 1-Propanol (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., 6.56 mass%) 2.0 g

[0250] Polyethylene glycol dodecyl ether (Brij L4, manufactured by Sigma-Aldrich, 4.59 mass %) 1.4 g

[0251] Reaction temperature: 30℃

[0252] Stirring speed: 300rpm

[0253] 0.04 g of EDOT, 1.4 g of Brij (registered trademark) L4, 2.0 g of 1-propanol, and 27 g of water were quantitatively added to a 50 ml screw-cap tube. The mixture was then stirred at 30° C. and 300 rpm. The texture derived from the super-swollen lamellar phase was confirmed using a polarizing plate, and a mixed solution having a super-swollen lamellar phase was obtained.

[0254] <Second step>

[0255] (That is, a second step of oxidatively polymerizing the 3,4-ethylenedioxythiophene contained in the 3,4-ethylenedioxythiophene layer using iron (III) chloride to form a nanosheet of poly (2,3-dihydrothieno-1,4-dioxin))

[0256] <Reagents used and reaction conditions>

[0257] Deionized water (3 ml)

[0258] FeCl3·6H2O (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) 0.0039 g

[0259] Reaction temperature: 30℃

[0260] Response time: 24 hours

[0261] It was confirmed that the reaction occurred while maintaining the bimolecular membrane.

[0262] 3 ml of an aqueous solution of iron (III) chloride was prepared from 0.0039 g of iron (III) chloride. The mixed solution obtained in the first step was heated to 30°C, and 3 ml of the aqueous solution of iron (III) chloride was added dropwise to the mixed solution at 30°C using a pipette.

[0263] <Third step>

[0264] (That is, a third step of removing the solvent from the solution containing the nano-sheet-like particles obtained in the second step and drying the solution)

[0265] The solvent, water, polymerization catalyst, surfactant, and amphiphilic substance added in the first step and the second step are removed by centrifugation. Ethanol and water are used as solvents for washing. The added solvent, water, surfactant, and amphiphilic substance are removed by ethanol, and the polymerization catalyst is removed by water. After washing, it can be stored as a dispersion liquid of ethanol or the like without drying. In addition, for drying, it is left to stand in an oven set at 90°C to volatilize the solvent.

[0266] <Evaluation Results>

[0267] The AFM measurement results are shown in Figures 1-2 .

[0268] According to the results of AFM measurement, the thickness was 2 nm, the maximum width in the plane direction was 800 nm, and the aspect ratio (maximum width in the particle / thickness) was 600.

[0269] The results of FT-IR measurements are shown in Figure 3 A peak derived from PEDOT was confirmed.

[0270] The results of TEM measurements are shown in Figures 4 to 6 The TEM measurement results confirmed the generation of nano-plate-like particles.

[0271] The DLS measurement results are shown in Figure 7 .

[0272] The results of TEM and DLS confirmed that the nanoparticles were in the form of flakes. The nanoparticles were composed of small nanoplatelets connected together, and the presence of a small amount of aggregates was confirmed.

[0273] The conductivity was measured and was about 1 S / cm.

[0274] The results of SEM-EDX measurements are shown in Figure 8 . Removal of impurities (Fe) was confirmed.

[0275] The results of TG determination are shown in Fig. 9 . The removal of iron was confirmed.

[0276] (Examples A-2 to A-3)

[0277] Nanosheet particles of PEDOT were obtained by the same method as in Example A-1 except that the amount of 1-propanol added as a surfactant was changed as shown in Table 1.

[0278] [Table 1]

[0279]

[0280] The evaluation criteria of "stability" in Table 1 are as follows.

[0281] ◎: Particularly ideal state

[0282] ○: Ideal state

[0283] (Examples B-1 to B-2)

[0284] Nanosheet particles of PEDOT were obtained by the same method as in Example A-1 except that the alcohol shown in Table 2 was used as a surfactant.

[0285] [Table 2]

[0286]

[0287] The evaluation criteria of "Expression of lamellar layers" in Table 2 are as follows.

[0288] ◎: Particularly ideal state

[0289] (Examples C-1 to C-5, Comparative Examples C-1 to C-6)

[0290] The nanosheet particles of PEDOT (3.4×10 -4 g) The obtained dispersion was dispersed in a solvent (1 ml) shown in Table 3 and Table 4 (Comparative Example). Dispersion in the solvent due to nanosheet-like particle formation was confirmed.

[0291] [Table 3]

[0292]

[0293] [Table 4]

[0294]

[0295] The evaluation criteria of the "dispersion degree" in Tables 3 and 4 are as follows.

[0296] ◎: Particularly ideal state

[0297] ○: Ideal state

[0298] △: Part of the ideal state

[0299] ×: Unsatisfactory condition

[0300] The evaluation criteria of "stability" in Tables 3 and 4 are as follows.

[0301] ◎: Particularly ideal state

[0302] ○: Ideal state

[0303] △: Part of the ideal state

[0304] ×: Unsatisfactory condition

[0305] The evaluation criteria of “electrical conductivity” in Tables 3 and 4 are as follows.

[0306] ◎: Particularly ideal state

[0307] ○: Ideal state

[0308] △: A state lower than the ideal state

[0309] (discuss)

[0310] The above results show that the obtained PEDOT nanosheet particles can be dispersed in a solvent without PSS, and the nanosheet particles are dispersed in both a polar solvent and a non-polar solvent.

[0311] (Example D-1)

[0312] (Production of Nanoplate-Shaped Particles of Polythiophene (PT))

[0313] <First step>

[0314] <Reagents used and reaction conditions>

[0315] Thiophene (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., 0.12 mass %) 0.0356 g

[0316] Deionized water (88.8 mass%) 27.0 g

[0317] Hexane (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., 0.042 mass%) 0.0127 g

[0318] 1-Propanol (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., 6.74 mass%) 2.05 g

[0319] Polyethylene glycol dodecyl ether (Brij L4, manufactured by Sigma-Aldrich, 4.31 mass %) 1.31 g

[0320] Reaction temperature: 30℃

[0321] Stirring speed: 300rpm

[0322] Thiophene 0.0356 g, Brij (registered trademark) L4 1.31 g, 1-propanol 2.05 g, hexane 0.0127 g, and water 27.0 g were quantitatively added to a 50 ml screw-cap tube. The mixture was then stirred at 30° C. and 300 rpm. The texture derived from the super-swollen lamellar phase was confirmed with a polarizing plate, and a mixed solution having a super-swollen lamellar phase was obtained.

[0323] <Second step>

[0324] <Reagents used and reaction conditions>

[0325] Deionized water (3 ml)

[0326] FeCl3·6H2O (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) 0.0010 g

[0327] Reaction temperature: 30℃

[0328] Response time: 24 hours

[0329] It was confirmed that the reaction occurred while maintaining the bimolecular membrane.

[0330] 3 ml of an aqueous solution of iron (III) chloride was prepared from 0.0039 g of iron (III) chloride. The mixed solution obtained in the first step was heated to 30°C, and 3 ml of the aqueous solution of iron (III) chloride was added dropwise to the mixed solution at 30°C using a pipette.

[0331] <Third step>

[0332] The solvent, water, polymerization catalyst, surfactant, and amphiphilic substance added in the first step and the second step are removed by centrifugation. Ethanol and water are used as solvents for washing. The added hexane, water, surfactant, and amphiphilic substance are removed by ethanol, and the polymerization catalyst is removed by water. After washing, it can be stored as a dispersion liquid of ethanol or the like without drying. In addition, for drying, it is left to stand in an oven set at 90°C to volatilize the solvent.

[0333] <Evaluation Results>

[0334] The AFM measurement results are shown in Fig.10 and Fig.11 .

[0335] According to the results of AFM measurement, the thickness was 3.5 nm, the maximum width in the plane direction was 150 nm, and the aspect ratio (maximum width in the particle / thickness) was about 40.

[0336] The results of TEM measurements are shown in Fig.12 The TEM measurement results confirmed the generation of nano-plate-like particles.

[0337] The DLS measurement results are shown in Fig.13 .

[0338] The results of TEM and DLS confirmed that the nanoparticles were in the form of flakes. The nanoparticles were composed of small nanoplatelets connected together, and the presence of a small amount of aggregates was confirmed.

[0339] (Example E-1)

[0340] (Measurement of the electrical conductivity of PEDOT nanoplate particles)

[0341] Nano-sheet-like particles of PEDOT were obtained by the same method as in Example A1. The electrical conductivity of the nano-sheet-like particles of PEDOT was measured by the measurement method described in the above [Measurement of Electrical Conductivity]. The results are shown in Table 5.

[0342] (Comparative Example E-1)

[0343] (Measurement of the electrical conductivity of PEDOT bulk particles)

[0344] PEDOT bulk particles were prepared in the same manner as in Example A-1 except that a solvent system containing no polyethylene glycol dodecyl ether was used, and the conductivity of the prepared PEDOT bulk particles was measured in the same manner as in Example E-1. The results are shown in Table 5.

[0345] [Table 5]

[0346]

[0347] <Discussion of Evaluation Results>

[0348] It was confirmed that the PEDOT nanosheet particles showed superior electrical conductivity compared to the PEDOT bulk particles.

[0349] (Example E-2)

[0350] The same PEDOT nano-plate-like particles as in Example E-1 were used to evaluate coating properties using the evaluation method described in the above [Evaluation of coating properties]. Visual observation confirmed that the coating properties were excellent in dispersion and uniformity.

[0351] The photo of the evaluation sample is shown in the BX-51 research microscope (manufactured by Olympus Corporation). Fig.14 .

[0352] (Comparative Example E-2)

[0353] The coating properties were evaluated by the same method as in Example E-2 using the same PEDOT bulk particles as in Comparative Example E-1. The visual observation results showed that the dispersion and uniformity were inferior to those in Example E-2.

[0354] The photo of the evaluation sample is shown in the BX-51 research microscope (manufactured by Olympus Corporation). Fig.15 .

[0355] <Discussion of Evaluation Results>

[0356] Fig.16 and 17 Schematic diagrams of the samples obtained in Example E-2 and Comparative Example E-2, respectively.

[0357] The results of Example E-2 and Comparative Example E-2 confirmed that the PEDOT nano-flake particles exhibited more excellent dispersion and uniformity than the PEDOT bulk particles.

[0358] Specifically, according to Fig.14 and Fig.15It can be seen from the microscope photograph that PEDOT nano-sheet particles can be evenly coated on the comb-shaped electrode without unevenness compared to PEDOT bulk particles. The reason may be that in the case of PEDOT bulk particles, the particle size is uneven, and the gaps between the particles become more during coating, while on the other hand, in the case of PEDOT nano-sheet particles, the thickness of the particles (i.e., sheets) is roughly uniform, so the particles are easy to fit together, and as a result, the gaps between the particles (sheets) become less during coating.

[0359] It should be noted that the results of the conductivity measurements of Example E-1 and Comparative Example E-1 above indicate that as the interparticle voids decrease, the contact resistance decreases, resulting in an increase in the conductivity of the PEDOT nanosheet particles and an improvement in the conductivity.

[0360] (Example E-3)

[0361] "The influence of manufacturing conditions (pH) on the appearance of PEDOT nanosheet particles"

[0362] EDOT (0.13 mass %), aqueous hydrogen peroxide solution (0.65 mass %), Brij L4 (4.57 mass %), 1-propanol (6.52 mass %), and phosphate buffer (88.1 mass %) pre-adjusted to various pH values ​​(pH 2, 3, 4, 5, 6, 7) were added to a screw-capped tube and mixed. The obtained mixed solutions were stirred at room temperature (25° C.). During the stirring, the birefringence derived from the super-swollen lamellar phase was confirmed while observing whether the super-swollen lamellar phase was present. The results are shown in Fig.18 .according to Fig.18 The evaluation results are shown in the following Table 6.

[0363] [Table 6]

[0364]

[0365] It should be noted that Fig.18 The evaluation criteria of "appearance of super-swollen lamellar phase" are as follows.

[0366] ○: Ideal state

[0367] △: Part of the ideal state

[0368] ×: Unsatisfactory condition

[0369] <Discussion>

[0370] according to Fig.18The results show that the super-swollen lamellar phase is observed at any pH value between pH 2 and 7, which is an ideal state (i.e., a state where thin nanosheets are stably produced), and it can be confirmed that the pH value has no effect on the super-swollen lamellar phase. In particular, at pH values ​​between pH 2 and 4, the state is particularly ideal (i.e., a state where the largest nanosheets are very stably produced), and it can be seen that it does not have a significant impact on the yield of PEDOT nanosheet particles.

[0371] (Example E-4)

[0372] "The influence of production conditions (pH) on the yield of PEDOT nanosheet particles"

[0373] EDOT (0.13 mass %), aqueous hydrogen peroxide solution (0.65 mass %), Brij L4 (4.57 mass %), 1-propanol (6.52 mass %), and phosphate buffer (88.1 mass %) adjusted to various pH values ​​(pH 2, 3, 4, 5) were added to a screw-capped tube and mixed. The obtained mixed solutions were stirred at room temperature (25° C.). During the stirring, the birefringence derived from the super-swollen lamellar phase was confirmed, and the formation of the super-swollen lamellar phase was observed.

[0374] After the above operation, an aqueous solution of ferric chloride was added to the obtained mixed solution. The obtained mixed solution was further stirred for 24 hours. After the stirring was completed, the recovered mixed solution was centrifuged at 11,000 rpm to recover the precipitate. The recovered precipitate was washed three times with ethanol and then dried. The mass of the dried product thus obtained was measured to calculate the yield of the obtained PEDOT nanosheet particles. The results are shown in Fig.19 .

[0375] <Discussion>

[0376] according to Fig.19 The results showed that the yield of PEDOT nanosheet particles was not significantly affected when the pH value was between pH 2 and pH 4.

[0377] (Example E-5)

[0378] "The effect of production conditions (addition of SDS) on the yield of PEDOT nanosheet particles"

[0379] EDOT (0.13 mass %), aqueous hydrogen peroxide solution (0.65 mass %), Brij L4 (4.57 mass %), 1-propanol (6.52 mass %) and water (88.1 mass %) were added to a screw-capped tube and mixed. The resulting mixed solution was stirred at room temperature (25° C.) to form a super-swollen lamellar phase.

[0380] Next, sodium dodecyl sulfate (SDS) was added to the mixed solution containing the super swollen lamellar phase so as to have various concentrations (0.098 mass %, 0.130 mass %, 0.147 mass %, 0.166 mass %, 0.180 mass %, 0.195 mass %), and mixed. The obtained mixed solutions were stirred at room temperature (25° C.). During the stirring, the birefringence derived from the super swollen lamellar phase was confirmed while the maintenance state of the super swollen lamellar phase was observed. The results are shown in Fig. 20 .according to Fig. 20 The evaluation results are shown in Table 7 below.

[0381] [Table 7]

[0382]

[0383] It should be noted that Fig. 20 The evaluation criteria of "maintaining state of super-swollen lamellar phase" are as follows.

[0384] ○: Ideal state

[0385] △: Ideal state in some cases

[0386] ×: Unsatisfactory condition

[0387] <Discussion>

[0388] according to Fig. 20 The results showed that when the SDS addition concentration was between 0.098 mass % and 0.147 mass %, it was in an ideal state (i.e., a state where thin nanosheets were stably produced). In addition, it was confirmed that they were all in a particularly ideal state (i.e., a state where the largest nanosheets were very stably produced), and that a highly stable super-swollen lamellar phase could be maintained.

Claims

1. Nano-flaky particles, characterized in that: It is a nano-sheet particle of a polythiophene compound. The thickness of the nano-plate-like particles is greater than or equal to 0.5 nm and less than or equal to 10 nm. The aspect ratio of the nanoplate-like particles is 100 or more.

2. The nano-plate-like particle according to claim 1, characterized in that: The polythiophene compound is poly(3,4-ethylenedioxythiophene).

3. The nano-plate-like particle according to claim 1 or 2, characterized in that: The thickness of the nano-plate-like particles is greater than 1 nm and less than 5 nm. The width of the nano-plate-like particles in the plane direction is 200 nm or more and 100 μm or less.

4. A method for producing nano-plate-like particles of a polythiophene-based compound, characterized in that: include: In a first step, a bimolecular membrane is formed in a solvent, and a thiophene compound is added to the solvent to form a super-swollen lamellar phase of the bimolecular membrane, thereby forming a layer of the thiophene compound between two monomolecular phases constituting one bimolecular membrane; and In the second step, the thiophene compound having formed a layer in the first step is subjected to oxidative polymerization using a polymerization catalyst to form nanosheet particles of a polythiophene compound.

5. The method for producing nano-plate-like particles of a polythiophene-based compound according to claim 4, wherein: In the first step, the super-swollen lamellar phase of the bimolecular membrane is formed under the temperature condition of 20° C. to 40° C.

6. The method for producing nano-plate-like particles of a polythiophene-based compound according to claim 4 or 5, wherein: The thiophene compound is 3,4-ethylenedioxythiophene, The polythiophene compound is poly(3,4-ethylenedioxythiophene).

7. The method for producing nano-plate-like particles of a polythiophene-based compound according to claim 4 or 5, wherein: The polymerization catalyst is iron (III) chloride.

8. The method for producing nano-plate-like particles of a polythiophene-based compound according to claim 4 or 5, wherein: The solvent is a solvent containing only water or a mixed solvent containing a hydrocarbon solvent and water, The mass ratio of the hydrocarbon solvent to water in the solvent is hydrocarbon solvent:water=0:100 to 15:

85.

9. The method for producing nano-plate-like particles of a polythiophene-based compound according to claim 4 or 5, wherein: The solvent is a mixed solvent comprising a hydrocarbon solvent and water, The mass ratio of the hydrocarbon solvent to water in the solvent is hydrocarbon solvent:water=0.01:99.99 to 15:

85.

10. The method for producing nano-plate-like particles of a polythiophene-based compound according to claim 9, wherein: The hydrocarbon solvent is hexane.

11. The method for producing nano-plate-like particles of a polythiophene-based compound according to claim 4 or 5, wherein: The amphiphilic substance constituting the bimolecular membrane is polyethylene glycol monoalkyl ether.

12. The method for producing nano-plate-like particles of a polythiophene-based compound according to claim 11, wherein: The polyethylene glycol monoalkyl ether is tetraethylene glycol monomethyl ether.

13. The method for producing nano-plate-like particles of a polythiophene-based compound according to claim 11, wherein: The polyethylene glycol monoalkyl ether is tetraethylene glycol monododecyl ether having a number average molecular weight of less than 362.

14. The method for producing nano-plate-like particles of a polythiophene-based compound according to claim 4 or 5, wherein: The solvent comprises a monohydric alcohol.

15. The method for producing nano-plate-like particles of a polythiophene-based compound according to claim 14, wherein: The monohydric alcohol is at least one selected from the group consisting of 1-propanol, 2-propanol, and 1-butanol.

16. The method for producing nano-plate-like particles of a polythiophene-based compound according to claim 14, wherein: The monohydric alcohol is 1-propanol.

17. The method for producing nano-plate-like particles of a polythiophene-based compound according to claim 15, wherein: In the solvent, the content of the monohydric alcohol is 0.1 mass % or more and 10 mass % or less.

18. The method for producing nano-plate-like particles of a polythiophene-based compound according to claim 4 or 5, wherein: The thickness of the nano-plate-like particles is greater than or equal to 0.5 nm and less than or equal to 10 nm. The width of the nano-plate-like particles in the plane direction is 200 nm or more and 100 μm or less. The aspect ratio (maximum width / thickness in the particle) of the nanoplate-like particles is 100 or more.

19. A dispersion composition comprising the nano-plate-like particles according to claim 1 or 2.

20. The dispersion composition according to claim 19, wherein It also contains a monohydric alcohol and is substantially free of water.

Citation Information

Patent Citations

  • Novel polythiophenes

    JP1989313521A

  • Method for manufacturing organic thin film, and organic device using the same

    JP2011181724A

  • Standing-wave excitation type electromagnetic wave electric discharge lamp

    JP2022165782A

  • Metal organic structure nanosheet and production method therefor

    WO2018016650A1

  • Sheet-like particles of zeolite and method for producing same

    WO2020250985A1